If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x(2x + -6) = 0 Reorder the terms: 4x(-6 + 2x) = 0 (-6 * 4x + 2x * 4x) = 0 (-24x + 8x2) = 0 Solving -24x + 8x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '8x'. 8x(-3 + x) = 0 Ignore the factor 8.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-3 + x)' equal to zero and attempt to solve: Simplifying -3 + x = 0 Solving -3 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + x = 0 + 3 x = 0 + 3 Combine like terms: 0 + 3 = 3 x = 3 Simplifying x = 3Solution
x = {0, 3}
| -4(-2x+7)=-12 | | 4(1+5r)=23+r | | 7x(x-1)=28 | | 4w^2+7w=-3 | | 4x*2+3x=3x*2-4x+18 | | -8r^2+9=6r | | 3x+1+x=49 | | 7+4x=-8+7(1+5x) | | -7(2(-5)+4)+10(-5)-9= | | 31-5x=10-8x | | 4y^2+11y+7=0 | | 4(2b-4)=2(a-5) | | 10x+y=-8 | | 4x+4=-8+5x | | 2=x-(-43) | | a^2x+x-1=a-2ax | | -x+35=3x+11 | | 36+8a=(3a+1) | | (3x-4)+(X)=148 | | -2+2x=5x-20 | | 7x+9=49+3x | | 25x^2-24x-9=-7x^2+12-18 | | 6=x/65 | | 2x-6=7x+14 | | 4x+14=-8x-2(7-4x) | | 36+8a=3(3a+1) | | -5x-9y=45 | | x-6=2x+5 | | 5-7(8y+6)= | | 11(2-9)+99-10(2)= | | 13k-130=201 | | 3x+5=-19+7x |